Lightweight authentication protocol for security vehicle network of railway freight train - Congdong LYU; Yucai LI (网络与信息安全学报)
With the development of railway transportation,it has put forward higher requirements for the safety of freight train.The present ground vehicle safety monitoring system,due to technical limitations,can’t meet the security requirement for real time information report of the train.Vehicular sensor can collect real-time vehicle information,to guarantee the safety of the train.Vehicle network is the basic of the communications between vehicular sensors.The basic of the security vehicle network for the railway freight train is authentication.Lightweight authentication protocol for the security vehicle network was proposed.The protocol can authenticate the network nodes without CA.